Patient preferences for active surveillance vs standard surgery after neoadjuvant chemoradiotherapy in oesophageal cancer treatment: The NOSANO‐study. Issue 6 (27th October 2022) - Hermus, Merel; van der Wilk, Berend J.; Chang, Rebecca T. H.; Collee, Gerlise; Noordman, Bo J.; Coene, Peter‐Paul L. O.; Dekker, Jan Willem T.; Hartgrink, Henk H.; Heisterkamp, Joos; Nieuwenhuijzen, Grard A. P.; Rosman, Camiel; Timmermans, Liesbeth; et al.
Abstract: Active surveillance may be a safe and effective treatment in oesophageal cancer patients with a clinically complete response after neoadjuvant chemoradiotherapy (nCRT). In the NOSANO‐study we gained insight in patients' motive to opt for either an experimental treatment called active surveillance or for standard immediate surgery. Both qualitative and quantitative analyses methods were used. Forty patients were interviewed about their treatment preference, 3 months after completion of nCRT (T1). Data were recorded, transcribed verbatim and analysed according to the principles of grounded theory. In addition, at T1 and T2 (12 months after completion of nCRT) questionnaires on health‐related quality of life, coping, anxiety and decisional regret (only T2) were administered. Interview data analyses resulted in a conceptual model with 'dealing with threat of cancer' as the central theme. Patients preferring active surveillance tend to cope with this threat by confiding in their bodies and good outcomes. Their mind‐set is one of 'enjoy life now'. Patients preferring surgery tend to cope by minimizing uncertainty and eliminating the source of cancer. Their mind‐set is one of 'don't give up, act now'. Furthermore, questionnaire results showed that patients with a preference for standard surgery had a lower quality of life. Patient preferences are individualized and thus difficult to predict. Our model can help healthcare professionals to determine patient preferences for treatment. Coping style and mind‐set seem to be determining factors here. Abstract : What's new? Active surveillance has become an alternative to standard surgery for oesophageal cancer patients with a clinically complete response after neoadjuvant chemoradiotherapy. This is the first study to explore the personal motivations for patients to opt for active surveillance or standard surgery. The results show that patients with a strong preference for active surveillance tend to cope with the threat of cancer by having faith in their bodies and good outcomes; patients with a strong preference for standard surgery tend to cope by minimizing the uncertainty. The model could support doctors and patients in reaching a well‐informed and personalized treatment decision.